Profile distributions of soil organic carbon fractions in a permafrost region of the Qinghai–Tibet Plateau. (8th April 2020) - Yuan, Zi‐Qiang; Jin, Hui‐Jun; Wang, Qing‐Feng; Wu, Qing‐Bai; Li, Guo‐Yu; Jin, Xiao‐Ying; Ma, Qiang
Abstract: Adequate characterization of soil organic carbon (SOC) fractions is essential to elucidate carbon dynamics in permafrost‐affected ecosystems. SOC and its fractions were investigated across alpine ecosystems, including alpine swamp meadows (ASM), alpine meadows (AM) and alpine steppes (AS), in permafrost regions on the Qinghai–Tibet Plateau (QTP), southwest China. The density separation method was used to separate the SOC into light‐ and heavy‐fraction organic carbon (LFOC and HFOC, respectively). Permafrost soils in the ASM had higher SOC, LFOC, and HFOC contents than in the AM. LFOC and HFOC contents were significantly correlated, but both were more closely related to SOC than to each other. On the ecological gradient from ASM to AS, the thickness of surficial organic horizons decreased while the thickness of mineral materials increased. SOC in the organic horizon and permafrost had high mineralization probability. At soil depths of 0–200 cm in ASM, AM, and AS, the SOC stocks were 123, 71, and 25 kg m −2 ; LFOC stocks were 70, 49, and 12 kg m −2 ; and HFOC stocks were 58, 37, and 15 kg m −2, respectively. These results show that SOC fractions vary with vegetation type and active layer thickness, thus making SOC sensitive to changes in environmental conditions. Therefore, the decomposition of SOC in permafrost‐affected soils of the QTP could be accelerated over a degrading permafrost and under a warming climate.